Penggunaan Aplikasi-Aplikasi Penerjemahan Bagi Pegawai Di DPRD Kota Bengkulu - Salam, Amanda Riskia; Putra, Dhanu Ario; Rullyanti, Merry; Sumantri, Ajis (LPPM Universitas Dehasen Bengkulu, 2024)
. Based on Law Number 17 of 2014 concerning the People's Consultative Assembly, the People's Representative Council, the Regional Representative Council and the Regional People's Representative Council and which has been passed down by the Regulation of the Bengkulu City Regional People's Representative Council, states that the DPRD consists of members of political parties participating in the General Election who elected based on the results of the General Election, and the DPRD is a regional people's representative institution whose position is as an element of regional government administration. In carrying out their activities, when employees have to work on things related to English, they always use applications or use web translators without knowing whether the translation results are correct or not. Through this KKN program, employees receive training so they are able to use applications and know about anything where Google could mistranslate.